2012
DOI: 10.3151/jact.10.195
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Self-Healing Capability of FRCC Using Different Types of Synthetic Fibers

Abstract: Experimental studies are carried out to evaluate the self-healing capability of FRCC using different types of synthetic fibers that have different chemical properties, i.e. poly vinyl alcohol (PVA), ethylene vinyl alcohol (EVOH), polyacetal (POM) and polypropylene (PP). FRCC specimens were subjected to tension tests in order to generate a crack, and the cracked specimens were immersed in water. In order to evaluate the effect of self-healing phenomena, permeability tests and microscopic observation were carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(47 citation statements)
references
References 12 publications
3
41
0
3
Order By: Relevance
“…The cracked part is also restored as a result, as reported for cracks that were narrower than 0.1 mm in earlier studies [10][11][12].…”
Section: Introductionsupporting
confidence: 53%
“…The cracked part is also restored as a result, as reported for cracks that were narrower than 0.1 mm in earlier studies [10][11][12].…”
Section: Introductionsupporting
confidence: 53%
“…(2) In ordinary SHCC, PVA fiber which has a hydroxide on the surface of the fiber, is normally used. Nishiwaki (2012) reported that PVA fibers become nuclei of healing product. Polyethylene fiber, however, does not have hydroxide, and thus offers lesser autogenous healing capability compared with ordinary SHCC with PVA fiber.…”
Section: Autogenous Healing Of Uhp-shcc and Its Advantagesmentioning
confidence: 99%
“…[9], carbon fibres [10], synthetic fibres (e.g., polypropylene, polyethylene, polyvinyl alcohol, etc.) [11], and metallic fibres ( [12][13][14][15][16][17]) are amongst the most used fibre-shaped reinforcements. Nevertheless, over the last few years, the high cost of the commercial fibres has promoted the use of recycled metallic waste [10,18] to develop new cement-based materials that are more resilient [12], environmentally friendly [13], and with advanced properties [18].…”
Section: Introductionmentioning
confidence: 99%